Role of Known Transient Receptor Potential Vanilloid Channels in Modulating Cardiac Mechanobiology - Miller, Michael; Koch, Sheryl E.; Veteto, Adam; Domeier, Timothy; Rubinstein, Jack (Frontiers in Physiology, 2021)
The Transient Receptor Potential (TRP) channels have been described in almost every mammalian cell type. Several members of the Vanilloid (TRPV) subtype have been found to play important roles in modulating cardiac function through calcium handling and structure under both physiologic and pathologic conditions in their response to systemic and local mechanobiological cues. In this review we will consider the most studied TRPV channels in the cardiovascular field; TRPV1 as a modulator of cardiac hypertrophy; TRPV2 as a structural and functional protein; TRPV3 in the development of hypertrophy and myocardial fibrosis; and TRPV4 in its roles modulating the fibrotic and functional responses of the heart to pressure overload. Lastly, we will also review the potential overlapping roles of these channels with other TRP proteins as well as the advances in translational and clinical arenas associated with TRPV channels.